Following the coins from the excavations at Khirbet Qumran (1951–1956) and Aïn Feshkha (1956–1958) - Callegher, Bruno (Novum testamentum et orbis antiquus, 2024)
The Qumran coins (hoard and single finds) are worthy of a novel. They were perfectly examined by H. Seyrig and A. Spijkerman, then the popular conviction spread that the coins had been lost. In fact, they were always kept where they had been classified. Now they are finally published and provide the possibility to suggest that Qumran was a very open centre for trade and transactions, at least from finally the end of the second century BC until the destruction of the site in 70/72 CE. This documentation provides a new reasoning on effective data – not on assumptions.